Assessment of Economic Greening Efficiency in Water Resource Management - Khumarova, Nina; Mahats, Nataliia; Kakabadze, Guram (Dr. Viktor Koval, 2025)
Introduction. Climate change, water depletion, environmental pollution, and rising economic activities in water use demand greener production. This emphasises the need for efficient methods and the assessment of economic greening in water use for sustainable development by advancing a sustainable blue economy. Aim and tasks. The study assesses the environmental efficiency of water use in Ukraine by analysing economic and environmental indicators. This study seeks to develop scientifically grounded methodological recommendations for improving enterprises' water use management. Results. This study conducted an economic and environmental analysis of water use across Ukraine’s economic sectors based on statistical data for 2022. The analysis utilised indicators such as water productivity by sector, economic productivity per unit of polluted wastewater, and share of capital investments in wastewater treatment within the total environmental protection investments. The results show that water, sewerage and waste management companies, which are natural monopolies, impact pollution, water abstraction and water resources. These enterprises were responsible for 72% of all the volume of polluted wastewater emitted and 35.28% of all water abstraction. The water productivity (USD 0.29/m³) and economic productivity (USD 1.85/m³) per unit of polluted wastewater were the lowest among all sectors. This indicates that the sector consumes a large volume of water relative to its economic contribution and exerts a significant adverse environmental impact owing to the high level of wastewater pollution. However, the sector’s share of capital investments in wastewater treatment within its total environmental protection investments was 59.76%. Conclusions. Based on the economic and environmental analysis of water use in the sectors of the Ukrainian economy, it is recommended that the level of influence of each enterprise in the sector on the state of water resources be assessed. Methodological recommendations for assessing the level of greening of economic activity in water use have been developed, consisting of four blocks: (i) assessment of water consumption efficiency; (ii) efficiency of wastewater management; (iii) compliance with regulatory requirements and social responsibility; (iv) assessment of innovations in the sphere of water use. Additionally, the calculation of an integrated indicator has been proposed, along with its interpretation according to an evaluation scale.